The Holy Trinity of Democracy, Economic Development, and Security: EU Democratization Efforts Beyond its Borders - The Case of Tunisia - Dandashly, Assem (2012)
Abstract: The EU has been engaged in democracy promotion, human rights, and civil liberties in the Mediterranean countries for over two decades with results ranging from very limited success to total failure. The revolutions in the Arab world – that have caught the EU and Western countries by surprise – provide a window of opportunity for real democratic reforms in the region. The successful democratization in Tunisia will send positive messages to the neighboring countries. Why should the EU be more involved in supporting Tunisia’s democratic transition? And what can the EU do to support Tunisia’s efforts to build and reform its institutions and to move towards a consolidated democracy with a functioning market economy? Answering these research questions requires understanding the major failures of the EU in the Mediterranean region – the Union of the Mediterranean is on hold and conditionality (at least political conditionality) is problematic and questionable. Prior to the Dignity Revolut